Вплив структури власності на ефективність корпоративного управління: вітчизняний та зарубіжний досвід - Чернова, І.В.; Чернов, М.В. (Економічний вісник Донбасу, 2025)
Досліджено вплив структури власності суб’єкта господарювання на ефективність корпоративного управління. Визначено основні критерії для визначення ефективності управління різними суб’єктами господарювання. Представлено порівняльний аналіз вітчизняного та зарубіжного досвіду корпоративного управління, який зосереджено на балансі контролю та захисті інтересів акціонерів, різноманітності підходів до організації власності в умовах різних господарських структур. Акцентовано увагу на ключових відмінностях національної та зарубіжної моделі корпоративного управління. Окреслено основні принципи для формування моделі оптимальної управлінської структури. Academic developments in the field of corporate governance and ownership structure are summarized. A number of topics that are considered by domestic scientists and require further study are highlighted. The influence of a company's ownership structure on the effectiveness of corporate governance is considered, as well as the direct relationship between them. A list of the most common indicators for determining management effectiveness is provided. It is shown that the ownership structure has a direct impact on the effectiveness of corporate governance. An analysis of types of ownership, their advantages and disadvantages is carried out. The main criteria for determining the effectiveness of management of various companies are determined. A list of the main foreign and domestic methods for analyzing the effectiveness of corporate governance is provided. A comparative analysis of domestic and foreign experience of corporate governance in various sectors of the economy is presented. The emphasis is on the dominance of the concentrated model in domestic governance, highlighting its historical characteristics and weaknesses. It is noted that foreign management practice prefers combined models, which opens up greater opportunities for adaptation and improvement of management. The basic principles of developing a model of the optimal management structure and the need for their comprehensive application are outlined. Based on the analysis of the specifics of management of domestic enterprises, the best examples of the application of modern management methods, as well as successes and difficulties in building a management system that meets modern challenges and takes into account the interests of all stakeholders, are identified. The results of the study are summarized and directions for further scientific development of corporate governance, its key factors and taking into account the specifics of the economy of a particular country are provided.